Preparation method and application of two-dimensional covalent organic framework solid solution
By regulating the monomer ratio of vinyl bond COFs solid solution, the fine regulation of its energy band structure is achieved, and the absorption capacity and carrier recombination problems of existing inorganic semiconductor materials during photocatalytic decomposition of water to produce hydrogen is solved, and the photocatalytic performance and hydrogen generation rate are significantly improved.
Patent Information
- Application Number
- CN202411958326.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing inorganic semiconductor materials have poor visible light absorption capacity and easy recombination of photogenerated carriers when photocatalyzed decomposition of water to produce hydrogen, which limits their practical application.
By changing the monomer ratio, fine regulation of the energy band structure of the vinyl-linked bond COFs solid solution is achieved, and COFs solid solution with a fully conjugated structure is formed, thereby improving its photocatalytic performance.
The activity of COFs solid solution in photocatalytic water decomposition and hydrogen production is improved, the hydrogen generation rate formed is significantly improved, and the synthesis process is simple and green.
Smart Images

Figure CN119684551A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of covalent organic framework materials, and specifically relates to a preparation method of a two-dimensional covalent organic framework solid solution and application thereof. Background Art
[0002] Hydrogen energy is a clean, sustainable, green energy with broad application prospects in energy storage, transportation, chemical industry, etc. As the world pays more and more attention to low-carbon development, green hydrogen with zero carbon emissions during production will occupy an important position in the future energy structure.
[0003] Photocatalytic decomposition of water to produce hydrogen can utilize the abundant solar energy and water resources on Earth, and is currently a major research hotspot. Among them, photocatalysts play a key role. 2 , ZnO, SrTiO 3 Inorganic semiconductor materials represented by Cd have poor visible light absorption and easy recombination of photogenerated carriers, which greatly limits the possibility of practical application. In order to improve the light absorption ability and photocatalytic activity of semiconductor materials, forming a solid solution is an effective strategy. For example, Cd x Zn 1-x S solid solution can achieve continuous regulation of the band structure by changing the value of x, thereby maximizing the photocatalytic performance.
[0004] Two-dimensional covalent organic frameworks (2D COFs) are crystalline porous materials formed by organic building blocks connected by covalent bonds. They have the advantages of designable structure, regular pores, high specific surface area and stability, and have been deeply studied in photocatalytic hydrogen production. The study of introducing solid solution strategy into COFs and then systematically regulating its properties and catalytic performance has not been reported so far. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a two-dimensional covalent organic framework solid solution and its application. The present invention achieves fine regulation of the energy band structure of the vinyl linker COFs solid solution by changing the monomer ratio, thereby improving the performance of photocatalytic water decomposition to produce hydrogen.
[0006] The method for preparing the two-dimensional covalent organic framework solid solution of the present invention comprises the following steps:
[0007] Step 1: Heat and stir 4,6-diaminoresorcinol dihydrochloride, yttrium trifluoromethanesulfonate, triethyl orthoacetate, dimethyl sulfoxide and pyridine to react. After the reaction, cool to room temperature, add water and extract with an organic solvent. After subsequent purification, a methyl-containing monomer is obtained for the synthesis of COFs solid solution.
[0008] Step 2: Add the monomer purified in step 1, trimesaldehyde TFB, 1,3,5-tri(4-formylphenyl)benzene TFPB and benzoic anhydride into a glass tube, heat to react under vacuum conditions, cool to room temperature after the reaction, collect the product, wash with methanol and tetrahydrofuran, vacuum dry and ball mill, differential centrifuge and vacuum dry again to obtain a COFs solid solution.
[0009] The synthesis route of the COFs solid solution is as follows:
[0010]
[0011] In step 1, the molar ratio of triethyl orthoacetate to 4,6-diaminoresorcinol dihydrochloride is 3:1 to 10:1, the molar ratio of pyridine to 4,6-diaminoresorcinol dihydrochloride is 2:1 to 2.5:1, and the molar amount of yttrium trifluoromethanesulfonate is 5%-10% of the molar amount of 4,6-diaminoresorcinol dihydrochloride.
[0012] In step 1, the reaction temperature is 55-80°C and the reaction time is 1-6 h.
[0013] In step 1, the organic solvent used for extraction is dichloromethane; the subsequent purification includes column chromatography and recrystallization, the column chromatography eluent consists of ethyl acetate and n-hexane in a volume ratio of 1:2-2:1, n-heptane is used for recrystallization, and the operating temperature is 90-110°C.
[0014] In step 2, the molar ratio of the methyl monomer to the aldehyde monomer is 3:2. The molar amount of the aldehyde monomer is based on the total molar amount of trimesaldehyde and 1,3,5-tri(4-formylphenyl)benzene.
[0015] Further, the molar ratio of trimesaldehyde to 1,3,5-tris(4-formylphenyl)benzene is 2:1 to 1:2, such as 2:1, 1:1 or 1:2.
[0016] Among them, 1,3,5-tri(4-formylphenyl)benzene or 5'-(4-formylphenyl)-[1,1':3',1''-triphenyl]-4,4''-dicarbaldehyde.
[0017] In step 2, the heating temperature is 180-200°C, the reaction time is 1-7 days, and the COFs solid solution is vacuum dried at 60-120°C.
[0018] Application of the two-dimensional covalent organic framework solid solution of the present invention in photocatalytic water decomposition to produce hydrogen.
[0019] The specific steps are as follows: add chloroplatinic acid, water and triethanolamine to the vacuum-dried two-dimensional covalent organic framework solid solution, transfer it to a photocatalytic reactor after ultrasonic dispersion, react with 300 W xenon lamp light under nitrogen atmosphere, and quantify the generated hydrogen by gas chromatography.
[0020] The beneficial effects of the present invention are embodied in:
[0021] 1. The present invention prepares a vinyl COFs solid solution by melt polymerization without using an organic solvent. The synthesis process is simple and green. The obtained COFs solid solution has high crystallinity and good porosity.
[0022] 2. The COFs solid solution of the present invention has a fully conjugated structure, and the particle size is reduced after ball milling, and the dispersibility in water is greatly enhanced, thereby showing high activity in photocatalytic water decomposition to produce hydrogen. The formation of solid solutions greatly enriches the types of COFs and provides new ideas for regulating the photoelectric properties of COFs and improving the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the monomer prepared in Example 1 of the present invention.
[0024] Figure 2 This is the X-ray powder diffraction pattern of the COFs solid solution prepared in Example 2-6 of the present invention.
[0025] Figure 3-7 This is the nitrogen adsorption-desorption curve of the COFs solid solution prepared in Example 2-6 of the present invention.
[0026] Figure 8 Fourier transform infrared spectra of three monomers used to prepare COFs solid solution in the present invention.
[0027] Fig. 9 This is the Fourier transform infrared spectrum of the COFs solid solution prepared in Example 2-6 of the present invention.
[0028] Fig.10 Comparison of the rates of photocatalytic decomposition of water to generate hydrogen by the COFs solid solutions prepared in Examples 2-6 of the present invention. DETAILED DESCRIPTION
[0029] Embodiment 1:
[0030] This embodiment provides a method for preparing a benzodioxazole-based monomer, comprising the following steps:
[0031] 1. Accurately weigh 1.196 g 4,6-diaminoresorcinol dihydrochloride (5.6 mmol) and 0.184 g yttrium trifluoromethanesulfonate (0.34 mmol) in a pre-dried 50 ml three-necked flask, add 10 ml triethyl orthoacetate (54.6 mmol), 10 ml dimethyl sulfoxide and 1.1 ml pyridine (13.6 mmol), heat to 80 °C under nitrogen atmosphere, stir and react, and monitor the reaction progress by thin layer chromatography.
[0032] 2. After the reaction is completed, cool to room temperature, add water, and extract with dichloromethane. Dry the organic phase with anhydrous sodium sulfate, and remove the solvent by rotary evaporator to obtain a crude product.
[0033] 3. The crude product was purified by silica gel chromatography with an eluent of n-hexane / ethyl acetate (1:1, v / v), and then recrystallized from n-heptane to obtain white crystals, which were recorded as c-MBO. The H NMR spectrum test showed the following results: Figure 1 . 1 HNMR (400 MHz, CDCl 3 ): δ 2.66 (6H, s), 7.57 (1H, s), 7.87 (1H, s).
[0034] Embodiment 2:
[0035] 34.8 mg c-MBO (0.185 mmol), 20 mg trimesaldehyde (0.123 mmol) and 84 mg benzoic anhydride (0.371 mmol) were weighed into a glass tube. The solid powder adhering to the inner wall was dropped to the bottom by ultrasonic treatment for a moment, and then the tube was evacuated and sealed with a flame. The sealed glass tube was placed in an oven at 200°C and reacted for 7 days. After cooling to room temperature, it was opened with a glass cutter, the solid was taken out, crushed and transferred to a mortar, and ground with methanol until there was no obvious granularity. It was washed by centrifugation three times with methanol and tetrahydrofuran, respectively, and dried to obtain a yellow powder, which was recorded as SS COF-1.
[0036] Embodiment 3:
[0037] 34.8 mg c-MBO, 13.3 mg trimesaldehyde (0.082 mmol), 16 mg 1,3,5-tri(4-formylphenyl)benzene (0.041 mmol) and 84 mg benzoic anhydride were weighed into a glass tube. Ultrasonication was applied for a moment to allow the solid powder adhering to the inner wall to fall to the bottom. Then, vacuum was evacuated and the tube was sealed with a flame. The sealed glass tube was placed in an oven at 200°C for 7 days. After cooling to room temperature, it was opened with a glass cutter, the solid was taken out, crushed and transferred to a mortar, and ground with methanol until there was no obvious granularity. It was washed by centrifugation three times with methanol and tetrahydrofuran respectively, and dried to obtain a yellow powder, which was recorded as SS COF-2.
[0038] Embodiment 4:
[0039] 34.8 mg c-MBO, 10 mg trimesaldehyde (0.061 mmol), 24 mg 1,3,5-tri(4-formylphenyl)benzene (0.061 mmol) and 84 mg benzoic anhydride were weighed into a glass tube, and the solid powder adhering to the inner wall was dropped to the bottom by ultrasonic treatment for a moment, and then the tube was evacuated and sealed with a flame. The sealed glass tube was placed in an oven at 200°C and reacted for 7 days. After cooling to room temperature, it was opened with a glass cutter, the solid was taken out, smashed and transferred to a mortar, and ground with methanol until there was no obvious granularity. It was washed by centrifugation three times with methanol and tetrahydrofuran, respectively, and dried to obtain a yellow powder, which was recorded as SS COF-3.
[0040] Embodiment 5:
[0041] 34.8 mg c-MBO, 6.7 mg trimesaldehyde (0.041 mmol), 32 mg 1,3,5-tri(4-formylphenyl)benzene (0.082 mmol) and 84 mg benzoic anhydride were weighed into a glass tube. The solid powder adhering to the inner wall was dropped to the bottom by ultrasonic treatment for a moment, and then the tube was evacuated and sealed with a flame. The sealed glass tube was placed in an oven at 200°C for 7 days. After cooling to room temperature, it was opened with a glass cutter, the solid was taken out, crushed and transferred to a mortar, and ground with methanol until there was no obvious granularity. It was washed by centrifugation three times with methanol and tetrahydrofuran, respectively, and dried to obtain a yellow powder, which was recorded as SS COF-4.
[0042] Embodiment 6:
[0043] Weigh 34.8 mg c-MBO, 48 mg 1,3,5-tri(4-formylphenyl)benzene (0.123 mmol) and 84 mg benzoic anhydride in a glass tube, sonicate for a moment to make the solid powder adhering to the inner wall fall to the bottom, then evacuate and seal the tube with flame. Place the sealed glass tube in an oven at 200°C and react for 7 days. After cooling to room temperature, use a glass cutter to open it, take out the solid, smash it and transfer it to a mortar, add methanol to grind until there is no obvious granularity, centrifuge and wash it three times with methanol and tetrahydrofuran respectively, and dry it to obtain a yellow powder, which is recorded as SS COF-5.
[0044] Embodiment 7:
[0045] This embodiment provides a step of ball milling treatment of COFs solid solution. The vacuum-dried COFs solid solution powder is evenly distributed in two ball mills, and the same number of ball milling beads and the same volume of ethanol are added, and the ball mills are fixed in a planetary ball mill. Ball milling is performed for 24 hours according to the set program. The ball mill is opened, the slurry is transferred to a centrifuge tube, and a smaller material is obtained by differential centrifugation, which is vacuum dried and set aside.
[0046] Embodiment 8:
[0047] This embodiment provides a step for using COFs solid solution to produce hydrogen by photocatalytic water decomposition. Accurately weigh 5 mg of COFs solid solution that has been ball-milled and vacuum-dried, add 15 ml of water, 3% mass fraction of chloroplatinic acid and 1.5 ml of triethanolamine, and transfer to a 160 ml quartz glass top-illuminated photocatalytic reactor after ultrasonic dispersion. Pass nitrogen for 15 min to remove the air in the reactor, then irradiate with a 300 W xenon lamp equipped with a > 380 nm filter for 2 h, and the generated hydrogen is quantified by gas chromatography.
[0048] Structural characterization:
[0049] 1. The COFs solid solution prepared in Example 2-6 was subjected to X-ray powder diffraction test. The results are as follows: Figure 2 As shown in the figure, all COFs solid solutions have high crystallinity. From SS COF-1 to SS COF-5, as the proportion of TFPB monomer increases, the diffraction peak corresponding to the (100) crystal plane moves to a lower angle, and the 2 Theta value decreases from 3.68° to 2.76°, which is consistent with the continuous increase in the lattice parameter. At the same time, SS COF-2 to SS COF-4 have only a single (100) peak, which is between SS COF-1 and SS COF-5, indicating that the two aldehyde monomers of different sizes, TFB and TFPB, are disorderly distributed in the lattice to form a COFs solid solution.
[0050] 2. The COFs solid solution prepared in Example 2-6 was subjected to several solvent exchanges with acetone, vacuum activated at 120°C for 12h, and then tested for nitrogen adsorption isotherms. The results are as follows: Figure 3-7 As shown in Figure 2, the prepared COFs solid solutions all have hysteresis loops, similar adsorption-desorption curves, and similar BET specific surface areas.
[0051] 3. Test the Fourier transform infrared spectra of the three monomers used to prepare COFs solid solution. The results are as follows: Figure 8 In the infrared of c-MBO, 2853 cm -1 and 2870 cm -1 They correspond to the symmetric stretching and antisymmetric stretching vibrations of CH in the methyl group; in the infrared of TFB, 1700 cm -1 Corresponding to the stretching vibration of C=O in the aldehyde group; in the infrared of TFPB, 1687 cm -1 Corresponding to the stretching vibration of C=O in the aldehyde group.
[0052] 4. The COFs solid solution prepared in Example 2-6 was mixed with KBr and ground, pressed into tablets, and tested for Fourier transform infrared spectroscopy. Fig. 9 As shown. Figure 8 Compared with the infrared spectrum of the monomers, SS COF-1 to SS COF-5 all have the peak at 1637 cm -1 A new absorption peak appeared near 1700 cm-1, which corresponds to the stretching vibration of C=C in COFs solid solution, indicating that COFs solid solution with vinyl linkage was successfully prepared. -1 There are also strong absorption peaks, indicating that there are more terminal aldehyde groups in the solid solutions of these COFs.
[0053] Catalytic performance:
[0054] The photocatalytic hydrogen production activity of COFs solid solution measured in Example 8 is as follows Fig.10 As shown in Figure 2, with the increase of TFPB content in COFs solid solution, the hydrogen generation rate presents a volcanic curve. Among them, SS COF-4 has the highest activity, reaching 3630 μmol·g -1 ·h -1 , the activity was increased by 110% and 225% compared with SS COF-1 and SS COF-5, respectively.
Claims
1. A method for preparing a two-dimensional covalent organic framework solid solution, characterized in that The steps include: Step 1: 4,6-diaminoresorcinol dihydrochloride, yttrium trifluoromethanesulfonate, triethyl orthoacetate, dimethyl sulfoxide and pyridine are heated and stirred for reaction. After the reaction is completed, the mixture is cooled to room temperature, water is added, and an organic solvent is used for extraction. After subsequent purification, a methyl-containing monomer is obtained for the synthesis of a covalent organic framework solid solution. Step 2: Add the monomer purified in step 1, trimesaldehyde TFB, 1,3,5-tri(4-formylphenyl)benzene TFPB and benzoic anhydride into a glass tube, heat to react under vacuum conditions, cool to room temperature after the reaction is completed, collect the product, wash with methanol and tetrahydrofuran, vacuum dry and ball mill, differential centrifuge and vacuum dry again to obtain a covalent organic framework solid solution.
2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of triethyl orthoacetate to 4,6-diaminoresorcinol dihydrochloride is 3:1 to 10:1, the molar ratio of pyridine to 4,6-diaminoresorcinol dihydrochloride is 2:1 to 2.5:1, and the molar amount of yttrium trifluoromethanesulfonate is 5%-10% of the molar amount of 4,6-diaminoresorcinol dihydrochloride.
3. The preparation method according to claim 1, characterized in that: In step 1, the reaction temperature is 55-80°C and the reaction time is 1-6 h.
4. The preparation method according to claim 1, characterized in that: In step 1, the organic solvent used for extraction is dichloromethane.
5. The preparation method according to claim 1, characterized in that: In step 1, the subsequent purification includes column chromatography and recrystallization, the column chromatography eluent is composed of ethyl acetate and n-hexane in a volume ratio of 1:2-2:1, and n-heptane is used for recrystallization at an operating temperature of 90-110°C.
6. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of the monomer purified in step 1 to the aldehyde monomer is 3:2, wherein the molar amount of the aldehyde monomer is based on the total molar amount of trimesaldehyde and 1,3,5-tri(4-formylphenyl)benzene.
7. The preparation method according to claim 6, characterized in that: The molar ratio of trimesaldehyde to 1,3,5-tri(4-formylphenyl)benzene is 2:1 to 1:
2.
8. The preparation method according to claim 1, characterized in that: In step 2, the heating temperature is 180-200°C and the reaction time is 1-7 d.
9. Use of the two-dimensional covalent organic framework solid solution prepared by any one of the preparation methods of claims 1 to 8 in photocatalytic water decomposition to produce hydrogen.
10. The use according to claim 9, characterized in that: Chloroplatinic acid, water and triethanolamine are added to the vacuum-dried two-dimensional covalent organic framework solid solution, and after being evenly dispersed by ultrasonic, the solution is transferred to a photocatalytic reactor and reacted under light irradiation in a nitrogen atmosphere.
Citation Information
Patent Citations
Preparation method of azo bond-rich covalent organic framework materials and application of azo bond-rich covalent organic framework materials in proton conduction and fuel cells
CN110982085A
Single-site transition metal covalent organic framework photocatalyst and preparation method thereof
CN111921559A
Covalent organic framework material containing oxadiazole connecting element
CN114085388A
Catalyst for fuel cell using porous material
JP2011042724A